Research Workshop for Research Grant - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
4 April 2012. A workshop to enhance the proposal for university’s grant was conducted at the Banquet Hall, Chancellery, for CMLHS lecturers. The workshop was spearheaded by none other than Associate Professor Dr Muhammad Nubli Abdul Wahab, CMLHS Deputy Dean (Research & Development).